1991
DOI: 10.1016/0165-2370(91)80075-j
|View full text |Cite
|
Sign up to set email alerts
|

Applications of analytical pyrolysis to the study of stony cultural properties

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Some of the most abundant thermochemolysis products are listed in Table 1. The chromatogram from Saint Denis black crusts compares well with previously published data from other European monuments [1,2,5,6]. Previous studies [6] have shown that the most abundant thermochemolysates in the black crusts from an Irish building were n-fatty acids, benzenecarboxylic acids, aliphatic dicarboxylic acids, and polycyclic aromatic hydrocarbons (PAH) having from two to five rings.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Some of the most abundant thermochemolysis products are listed in Table 1. The chromatogram from Saint Denis black crusts compares well with previously published data from other European monuments [1,2,5,6]. Previous studies [6] have shown that the most abundant thermochemolysates in the black crusts from an Irish building were n-fatty acids, benzenecarboxylic acids, aliphatic dicarboxylic acids, and polycyclic aromatic hydrocarbons (PAH) having from two to five rings.…”
Section: Resultssupporting
confidence: 82%
“…Wet and dry deposition processes combined with gypsum crystal growth result in the formation of a hard, grey to black crust, in which airborne organic pollutants, aerosols, and a wide range of particulate matter, including dust, pollen, and spores, are entrapped in the mineral matrix. Black crusts cover marble, limestone, sandstone, granite, and terracotta statues, and have also been observed on bronze statues, tiles, bricks, and glass windows [1].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A n aliquot of the extract was injected into a GUMS system. Methods and analytical conditions have been thoroughly described elsewhere (8). Separation and identification of the compounds was achieved using a fused-silica capillary column (25m x 0.32 mmi.d.1 coatedwithCPSil5.…”
Section: Methodsmentioning
confidence: 99%
“…Py-GC-MS is a powerful sample preparation, separation, and identification technique often utilized to characterize relatively high molecular weight materials like polymers. In archaeological and museum sciences, py-GC-MS has been used in the study of artists' materials [21][22][23][24][25][26], resinous materials [27][28][29][30], and black encrustations on or near cultural properties [18,31,32]. Of particular relevance to characterizing the 10BT1 coating, organic residues on pottery, including those formed during cooking, have been studied using py-GC-MS [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%